METHOD FOR MASS BREEDING OF THE EGG PARASITE Telenomus alsophilae - BUSTILLO, ALEX E. (Revista Colombiana de Entomología, 1978)
The author describes in detail the techniques for the mass rearing of Telenomus alsophilae as an egg parasite of the giant looper, Oxydia trychiata, an important pest of forest plants in Colombia. It is concluded that the technique suggested is simple, cheap, and that it could be an important tool in future control strategies.